Pengembangan E-Booklet Berbasis CCE (Cooperative Class Experiment) Tipe Group Investigation Yang Berorientasi Pada Keterampilan Generik Sains Peserta Didik SMP - Suci Rahayu; Sjaifuddin Sjaifuddin; Annisa Novianti Taufik (PendIPA Journal of Science Education, 2026)
Generic science skills are considered as one of the skills that are considered to be required by students in this century because with these skills the learning process can be more meaningful and students can learn through their own experiences. However, currently generic science skills in one of the schools in Banten have not been achieved due to several factors, namely the teaching materials and learning strategies used in the learning process have not supported the development of students' generic science skills. Based on these problems, an e-booklet teaching material based on CCE (Cooperative Class Experiment) Group Investigation type was developed which was designed to develop junior high school students' generic science skills. The purpose of this study was to analyze the level of product validation and to determine students' responses to the developed teaching materials. The research method used is Research and Development (R&D) using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) but limited only to the Implementation stage on a small scale to determine students' responses. The results of this study indicate that the CCE (Cooperative Class Experiment) Group Investigation-based e-booklet obtained a percentage of 88.20% which is categorized as "Very Valid" including the validation results of teaching material experts, material experts and practitioners. Then, after going through a revision process from the experts, the product was tested on students on a small scale and obtained a percentage of 84.23% with the "Very Valid" category. Thus, the CCE (Cooperative Class Experiment) Group Investigation-based e-booklet is declared suitable for use as teaching material.